Synthesis, characterization and crystal structure of 2-(4-(methylthio)phenyl)-1H-benzo[d]imidazole - Ziaulla, Mohamed; Manjunatha, Maralavadi Nagaraju; Nagasundara, Kuderu Rajendraswamy; Begum, Noor Shahina (European Journal of Chemistry, 2011)
An efficient synthesis of the title compound, 2-(4-(methylthio)phenyl)-1H-benzo[d]imidazole, was carried out by the condensation reaction of o-phenylenediamine and p-thiomethyl benzaldehyde in benzene. The structure was confirmed by spectroscopic data and elemental analyses. The molecular structure was determined from single crystal X‐ray diffraction data. The compound crystallizes in the orthorhombic space group Pbca with a = 8.544(2) Å, b = 9.700(3) Å, c = 29.684(8) Å, V = 2460.0(11) Å3, Z = 8. The crystal structure is stabilized by intermolecular C-H…N, N-H…N and π-π interactions.